Strategi Peningkatan Pertumbuhan Ekonomi Di Indonesia Melalui Kebijakan Ekspor Impor Dalam Bisnis Internasional - Siti Maysarah; Hendra Ibrahim (Jurnal Publikasi Ilmu Manajemen, 2024)
A country's success can be reflected through its economic growth, which is measured from aspects such as the value of exports and imports which influence the trade balance. Success is achieved when industry is supported by solid economic strength, requiring the government's commitment to providing positive policies to encourage rapid and stable economic growth, especially in the context of international trade or business. With positive economic growth, national income will increase and create economic prosperity for society. Studies in the last decade show that exports drive economic growth by generating foreign exchange, which can be used to support domestic development and finance imports. The aim of this research is to determine strategies for increasing economic growth through export-import policies in Indonesia. This research uses a literature review approach in data collection and analysis. The research results show that exports in Indonesia are still low compared to other countries in the world, one of which is due to policies that are not in accordance with public policy theory.